INTERAKSI SOSIAL DALAM ORGANISASI HIMPUNAN PEMUDA PELAJAR MAHASISWA INDRAGIRI HILIR PERIODE 2017-2019 DI PEKANBARU - M Wendi Fitranda; Daeng Ayub; Desti Irja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : The purpose of this study was to determine the level of social interaction in the organization of the student youth association of Indragiri Hilir students for the 2017-2019 period in Pekanbaru and determine or analyze the contribution of indicators as a factor on the variables of social interaction in the organization of the student youth association of Indragiri Hilir students for the 2017-2019 period in Pekanbaru. The sample in this study amounted to 41 people using sample random sampling. Data collection techniques used are questionnaires containing 50 questions. Data analysis techniques use the SPSS program and percentage calculation. The results of this study indicate that the social interaction of student youth association of Indragiri Hilir students for the 2017-2019 period in Pekanbaru is classified as being seen from the indicators of cooperation, competition and conflict.Key Words: Social Interaction, Organization, Indragiri Hilir Student College Student Association